Impact of Vortioxetine on Synaptic Integration in Prefrontal-Subcortical Circuits: Comparisons with Escitalopram - Chakroborty, Shreaya; Geisbush, Thomas R.; Dale, Elena; Pehrson, Alan L.; Sánchez, Connie; West, Anthony R. (Frontiers in Pharmacology, 2017)
Prefrontal-subcortical circuits support executive functions which often become dysfunctional in psychiatric disorders. Vortioxetine is a multimodal antidepressant that is currently used in the clinic to treat major depressive disorder. Mechanisms of action of vortioxetine include serotonin (5-HT) transporter blockade, 5-HT1A receptor agonism, 5-HT1B receptor partial agonism, and 5-HT1D, 5-HT3, and 5-HT7 receptor antagonism. Vortioxetine facilitates 5-HT transmission in the medial prefrontal cortex (mPFC), however the impact of this compound on related prefrontal-subcortical circuits is less clear. Thus, the current study examined the impact of systemic vortioxetine administration (0.8 mg/kg, i.v.) on spontaneous spiking and spikes evoked by electrical stimulation of the mPFC in the anterior cingulate cortex (ACC), medial shell of the nucleus accumbens (msNAc), and lateral septal nucleus (LSN) in urethane-anesthetized rats. We also examined whether vortioxetine modulated afferent drive in the msNAc from hippocampal fimbria (HF) inputs. Similar studies were performed using the selective 5-HT reuptake inhibitor (SSRI) escitalopram (1.6 mg/kg, i.v.) to enable comparisons between the multimodal actions of vortioxetine and SSRI-mediated effects. No significant differences in spontaneous activity were observed in the ACC, msNAc, and LSN across treatment groups. No significant impact of treatment on mPFC-evoked responses was observed in the ACC. In contrast, vortioxetine decreased mPFC-evoked activity recorded in the msNAc as compared to parallel studies in control and escitalopram treated groups. Thus, vortioxetine may reduce mPFC-msNAc afferent drive via a mechanism that, in addition to an SSRI-like effect, requires 5-HT receptor modulation. Recordings in the LSN revealed a significant increase in mPFC-evoked activity following escitalopram administration as compared to control and vortioxetine treated groups, indicating that complex modulation of 5-HT receptors by vortioxetine may offset SSRI-like effects in this region. Lastly, neurons in the msNAc were more responsive to stimulation of the HF following both vortioxetine and escitalopram administration, indicating that elevation of 5-HT tone and 5-HT receptor modulation may facilitate excitatory hippocampal synaptic drive in this region. The above findings point to complex 5-HT receptor-dependent effects of vortioxetine which may contribute to its unique impact on the function of prefrontal-subcortical circuits and the development of novel strategies for treating mood disorders.